"Pony Up!" Managing Destitution among Grooms from Australia in British India. (1st May 2022) - Datta, Arunima
Abstract : This article examines the history of Australian horse-grooms who travelled to India, but often ended up destitute, at least for brief periods, before travelling on or settling in India. This case study of destitute Australian horse-grooms in British India provides a lens to explore intercolonial politics within the British Empire, particularly the complex socio-political dynamics of intercolonial labour migration during the later nineteenth century. In so doing, the different ways class and race intersected in Australia and India, and the conflicts between colonial governments that stemmed from these differences, are revealed. Vagrant European horse-grooms were regarded as both a problem and in need of assistance in India, while in Australia they were simply regarded as the undeserving poor.